Assessing Soil Nutrients Variability and Adequacy for the Cultivation of Maize, Cassava, and Sorghum in Selected Agroecological Zones of Cameroon. (28th December 2020) - Nanganoa, Lawrence T.; Ngome, Francis A.; Suh, Christopher; Basga, Simon D.
Abstract : Access to information on soil nutrients status and variability is essential in understanding the potential of soils and their responsiveness to management interventions in agriculture. The current study evaluated soil nutrients status in selected agroecological zones (AEZs) of Cameroon and identified variations and their adequacy for maize ( Zea mays L.), sorghum ( Sorghum bicolor L. (Moench)), and cassava ( Manihot esculenta Crantz) production. A total of 163 soil samples were collected from surface (0–15 cm) layer for the determination of pH, organic matter (OM), estimated nitrogen release (ENR), sulphur (S), calcium (Ca), magnesium (Mg), potassium (K), sodium (Na), boron (B), iron (Fe), manganese (Mn), copper (Cu), zinc (Zn), aluminium (Al), phosphorus (P), total exchangeable capacity (TEC), and base saturations. The results showed different degrees of variability in soil nutrients ranging from low to very high in all the AEZs. The soils in all the AEZs were consistently deficient in available phosphorus, sulphur, boron, and zinc in varying proportion and might be inadequate to supply cultivated maize, sorghum, and cassava with the nutrients needed to achieve optimal growth. The soils were also prone to Mg-induced K deficiency, which could limit the growth of maize, sorghum, or cassava. These results therefore suggest that management of inherent soil properties should be based on-site specific situations.